The instuments of the convergence of budgetary policies in the WAEMU aera - (:unkn) unknown (My University, 2016)
Legal studies on African Public Finance rarely address fiscal policy issues. The economic nature of this subject isprobably the reason. Yet the creation of economic integration space between states sharing the same currency led the law,including community law, to take a firm hold on fiscal policy issues. Any fiscal laxity from a state has repercussions on theothers and the stability of the monetary Union. The strengthening of economic integration, in west Africa, with the WAEMUTreaty of 1994 has been accompanied by the setting up of a converging measures of budgetary policies of states members. This consists in monitoring, through a community institutional framework, compliance by states with some criteria, mainlybudgetary. The convergence of budgetary policies thus refers to common budgetary discipline to be observed by the statesmembers of the WAEMU area. The establishment of such measures necessarily ends at the normative level by thetransformation of public finance law of states. The compliance with community budget discipline goes through self-discipline that states must self-impose in the management of their public finances. This new community power has an effect on national finance through their content, their public policy choices and management techniques. The aim of this study is to take an interest in one of the determining transformations factors of national public finance management systems in the states members of the WAEMU area.
Keywords: African Research